Manajemen Pembelajaran Biologi Menggunakan Power Point - Abdurahmansyah Abdurahmansyah; Irham Falahudin; Dian Robian (Program Magister Manajemen Pendidikan Islam Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2021)
This study aims to describe the management of biology learning using power points at Madrasah Aliyah Negeri 2 Ogan Komering Ilir which includes planning, implementation and evaluation. This research is a descriptive research with a qualitative approach. The subjects of this study were the principal, vice principal of the curriculum section, Biology subject teachers, staff staff, students related to the implementation of Biology learning. Data collection techniques used interviews, observation and documentation. Test the validity of the data using the source triangulation technique. The results showed that before teaching the teacher had to plan in advance the syllabus, prota, lesson plans and other learning tools. Implementation in biology learning must also be planned, so that students can receive learning effectively and efficiently so that learning objectives can be implemented. The evaluation carried out must also be in accordance with the planning and implementation, this learning evaluation can be carried out including collecting data about activities or giving questions to students, either individually or in groups and seeing the time efficiency of using the media used in an effort to achieve the learning objectives that have been set in the learning process. learning program. In the evaluation stage, the teacher first conveys all the material related to the subject matter. Furthermore, after the teacher gave the subject matter using the power point media used, the biology teacher directly gave questions to one of the students to answer questions that had to do with the material being taught using the power point.